The Effect of Type and Mode of Light Curing Units on Degree of Conversion of Bulk Fill Composites - Razieh Hoseinifar; Lida Lashkarizadeh (Isfahan University of Medical Sciences, 2022)
Adequate polymerization is a critical factor in obtaining optimal physical and mechanical properties and a satisfying clinical outcomes in composite restorations. The aim of this study was to evaluate the effect of type and mode of light curing units on degree of conversion (DC) of Bulk Fill composites (Xtra-fill andTetric N-Ceram Bulk Fill) compared to conventional composite (Tetric N-Ceram).Materials & Methods:This in-vitro experimental study was conducted in Kerman and Tehran School of Dentistry in 2019. Number of 15 uncured composites and 45 composite discs were fabricated using the Teflon molds with a 4 mm thick and 10 mm diameter and light cured from the top using LED ramp, LED and QTH curing units for 20 seconds. Bulk Fill composites (Xtra-fill andTetric N-Ceram Bulk Fill) were placed with a 4mm_thick increment and conventional composite (Tetric N-Ceram) was placed incrementally (with 2 mm thickness in each layer). The degree of conversion of top and bottom surfaces of composites were measured usi-0.05.Results:In all samples, the DC value of top surfaces was significantly higher thanthe 4mm depth (p value < 0.05). Overall, there were no significant difference between the DC value of tested composites (p value > 0.05), But LED light in ramp mode showed significantly better results compared to LED and QTH light sources (p value < 0.05). The type and mode of light cure units had no influence on DC of bulk fill composites (p value > 0.05), but the DC of conventional composite with QTH and LED ramp was significantly higher than LED (p value < 0.05).Conclusion:The results of this study showed that the DC value of bulk fill composites were not significantly affected by the type and mode of light cure units, and all investigated bulk fill composites obtained clinically acceptable degree of conversion at 4 mm depth